(untitled) (Revista científica Olimpia, 2019)
The objective of this study was to establish the functional assessment of the motor components that determine postural control and sarcopenia levels in athletes of the women’s basketball team of the University of the Atlantic. We evaluated 13 athletes in which techniques were used for the assessment and collection of data, among the results obtained significant differences were found in most of the variables studied in athletes, Endomorphic somatotype is predominant, which confirms a large adipose mass found in those evaluated. About podometry, a predominance of foot type with a tendency to cavity was obtained. Concerning the functional assessment of the movement, it was found that within the tests included in this test, most athletes perform them correctly without any type of asymmetry or compensation. Concerning sarcopenia, variables were taken into account for bioimpedance and the cross-sectional area of the arm, thigh, and leg, resulting in an average index of 5.51+/- 0.525 kg/m2 being located above the cut-off points referenced in the study.